THE USE OF MACRO-ERGONOMIC WORK SYSTEM DESIGNS TO REDUCE MUSCULOSKELETAL DISORDERS AND INJURY RISK IN TRAINING - Purnomo, Hari; Giyono, Edi; Apsari, Ayudyah Eka (The South African Journal of Industrial Engineering, 2017)
Training based on competency is a government effort to improve employee candidates’ job competence. The T echnical Implementation Unit of the Technopark Ganesha Sukowati Sragen is a training centre in the Sragen Regency. Ergonomic issues have still not received attention in some training programmes. The work system design is constructed to support the achievement of the agency’s vision and mission, using the macro-ergonomic analysis and design approach (MEAD). Research results show that the key variance is the installation of embroidery hoops, which is difficult and time-consuming. Integration of the work system with ergonomic designs is necessary to create a pleasant training environment and to improve job competence. The new designs include adjustable seats, embroidery hoops tables with a foot rest, improved lighting, facemasks, earplugs, and a drinking water facility. The workshop layout is designed to follow the work process. The trainees also participated in stretching exercises before training began. A t-test was conducted with the same research design and the same subject, and the results showed a reduction of up to 60.39 per cent in musculoskeletal disorders and a reduction of up to 22.2 per cent in the risk of injury.